Método para la producción de formulaciones inyectables de productos proteicos hemoderivados y productos obtenidos utilizando dicho método - Segura Ruiz, Álvaro (2011)
The invention relates to a method for producing injectable pharmaceutical formulations of blood-derived protein materials, including the steps of fractioning the source material in a polymer/salt aqueous two-phasesystem in the presence of phenol, purifying the top phase of the system by means of precipitation with caprylic acid and purifying the bottom phase by means of thermocoagulation, increasing the purity of the materials in both phases through chromatography, removing viral particles by means of the nanofiltration of both preparations, and formulating, stabilizing, and packaging the resulting materials.